2009
DOI: 10.1007/s10195-009-0060-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anemia at admission and outcome in patients older than 60 years with hip fracture

Abstract: Background We have reported that the functional outcome in elderly with hip fracture is related to age at admission, dementia, and anemia. In this study, we examined the relationship between hemoglobin level at admission and walking ability, as well as survival outcome at discharge. Materials and methods We studied 394 patients aged 60 years or older treated at our hospital for hip fracture since 1997. Anemia was defined as an admission hemoglobin level\13.0 g/dl for men and\12.0 g/dl for women. The relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 13 publications
3
36
2
4
Order By: Relevance
“…In contrast to our findings, Hagino et al [17], who compared the outcome of patients with mild and severe anemia, reported no significant difference in ambulatory status at discharge between the two groups of patients. The study of Hagino et al [17] did not exclude patients who were non-ambulatory prior to fracture as well as patients treated non-operatively. The potential confounding effect of the heterogeneous nature of the population group [17] needs to be taken into account when comparing the results of this study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to our findings, Hagino et al [17], who compared the outcome of patients with mild and severe anemia, reported no significant difference in ambulatory status at discharge between the two groups of patients. The study of Hagino et al [17] did not exclude patients who were non-ambulatory prior to fracture as well as patients treated non-operatively. The potential confounding effect of the heterogeneous nature of the population group [17] needs to be taken into account when comparing the results of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Anemic patients in our study revealed to sustain more often an intertrochanteric fracture, which is consistent with the findings of previous studies [15,17]. The reason for this could possibly be explained in two ways.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations